SHARK FINNING SEBAGAI ISU GLOBAL PENYEBAB KEPUNAHAN HIU DI DUNIA - Tika Dian Pratiwi (The Indonesian Islamic Studies and International Relations Association (Insiera), 2016)
This article explores about the shark finning, a an activity of shark hunting in order to remove and retent its fins for commercial purpose. Rumor has spead that shark fin is good for healthy. Meanwhile, based on researchs and experts, the shark actually contains high methyl mercury that is dangerous for humans. The echo-sounding is the activity of shark finning, believed for sustaining the economy of the fishermen. This is not entirely true since the fishermen still have sufficient income without doing shark finning. This article explains that taking advantage from the shark conservation is a good alternative for the livelihood of fishermen and also for the survival of sharks. Shark population has declined even closer to the extinction due to shark finning. Shark extinction would damage the marine eco-system since the sharks are giving many benefits for the marine eco-system due to its position as the top predators in the marine food chain. The government issued various policies to support the global fight against shark finning. Non-governmental organizations are also advocating the same mission, to protect sharks from extinction. However, the number of regulations and sharks safeguarding activities will not be effective without good cooperation with the fishermen or those who are hunting sharks irresponsibly.